Peaks and valleys : making good and bad times work for you - at work and in life - Johnson, Spencer (New York, United States : Atria Books, 2009)
A story of a young man who lives unhappily in a valley until he meets an old man who lives on a peak, and it changes his work and life forever. Initially, the young man does not realize he is talking with one of the most peaceful and successful people in the world. However, through a series of conversations and experiences that occur up on peaks and down in valleys, the young man comes to make some startling discoveries. Eventually, he comes to understand how he can use the old man's principles and practical tools in good and bad times, and becomes more calm and successful himself.--From publisher description
Includes bibliographical references and index
BSBA
Keywords: Success in business; Success